Transforming opera ... from high art to people's art ... - De Jager, Salomon van Niekerk (My University, 2010)
The aim of this research report will be to determine: The repositioning of opera as a genre in the Free State to ensure its survival; Intended and / or unintended consequences of The White Paper on Arts, Culture and Heritage, 4 June 1996, that sanctioned the survival of opera in the Free State.
MA Faculty of Humanities, Univerasity of the Witwatersrand, 2009.
Keywords: transforming opera